Urgensi Regulasi Perampasan Aset dalam Sistem Hukum Indonesia untuk Mendukung Kesejahteraan Rakyat - Djamal Djamal; Martomo (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the urgency of enacting the Asset Confiscation Bill in optimizing the recovery of state losses and to examine the position of the Asset Confiscation Bill as a national legal framework in relation to existing sectoral regulations. This research employs a normative juridical approach with a descriptive-analytical method. The legal materials used consist of primary and secondary legal materials, which are analyzed qualitatively through the theory of legal protection, Lawrence M. Friedman’s theory of the legal system and the theory of justice. The novelty of this study lies in its mapping of the Asset Confiscation Bill not merely as an additional instrument in corruption eradication, but as a national legal framework that integrates asset recovery mechanisms currently dispersed across the Criminal Code, the Criminal Procedure Code, the Anti-Corruption Law and the Anti-Money Laundering Law. The findings show that the main weakness of Indonesia’s asset confiscation system lies in its dependence on the mechanism of criminal forfeiture, which often obstructs asset recovery when the offender dies, flees, transfers the assets, or when the criminal process has not yet resulted in a final and binding court decision. The Asset Confiscation Bill introduces a legal reform through the mechanism of non-conviction based asset forfeiture using an in rem approach, which places the asset as the object of examination without eliminating the protection of the rights of bona fide owners. This study also finds that the Bill performs a harmonizing function, as it regulates in a more integrated manner the stages of asset tracing, freezing, seizure, confiscation, management and recovery, while also clarifying coordination among law enforcement institutions. Therefore, the enactment of the Asset Confiscation Bill is necessary to strengthen legal certainty, enhance the effectiveness of state loss recovery and protect the public interest.